Climate Change Increasing Calcium and Magnesium Leaching from Granitic Alpine Catchments - Kopáček, Jiří; Kaňa, Jiří; Bičárová, Svetlana; Fernandez, Ivan J; Hejzlar, Josef; Kahounová, Marie; Norton, Stephen A; Stuchlík, Evžen (Environmental science & technology, 2017)
Climate change can reverse trends of decreasing calcium and magnesium [Ca + Mg] leaching to surface waters in granitic alpine regions recovering from acidification. Despite decreasing concentrations of strong acid anions (-1.4 μeq L-1 yr-1) during 2004-2016 in nonacidic alpine lakes in the Tatra Mountains (Central Europe), the average [Ca + Mg] concentrations increased (2.5 μeq L-1 yr-1), together with elevated terrestrial export of bicarbonate (HCO3-; 3.6 μeq L-1 yr-1). The percent increase in [Ca + Mg] concentrations in nonacidic lakes (0.3-3.2% yr-1) was significantly and positively correlated with scree proportion in the catchment area and negatively correlated with the extent of soil cover. Leaching experiments with freshly crushed granodiorite, the dominant bedrock, showed that accessory calcite and (to a lesser extent) apatite were important sources of Ca. We hypothesize that elevated terrestrial export of [Ca + Mg] and HCO3- resulted from increased weathering caused by accelerated physical erosion of rocks due to elevated climate-related mechanical forces (an increasing frequency of days with high precipitation amounts and air temperatures fluctuating around 0 °C) during the last 2-3 decades. These climatic effects on water chemistry are especially strong in catchments where fragmented rocks are more exposed to weathering, and their position is less stable than in soil.
Keywords: podnebí; Calcium; vápník; monitorování životního prostředí; hořčík; Environmental Monitoring; Climate Change; Soil; Magnesium; jezera; klimatické změny; půda; Lakes; Climate